[OP.2C.03] THE INFLAMMATORY COMPONENT OF CARDIOVASCULAR AGEING ON ALBUMINURIA AND ARTERIAL STIFFNESS IN ESSENTIAL HYPERTENSIVE SUBJECTS. (September 2017) - Dimitriadis, K.; Tsioufis, C.; Kasiakogias, A.; Kalos, T.; Kouremeti, M.; Syrmali, K.; Leontsinis, G.; Konstantinidis, D.; Andrikou, E.; Tousoulis, D.
Abstract : Objective: In the present study, we examined the interrelationships between aging, high-sensitivity C-reactive protein (hs-CRP), urinary albumin excretion expressed as the albumin to creatinine ratio (ACR), and arterial stiffness in essential hypertensive patients. Design and method: 295 newly diagnosed untreated non-diabetic patients with stage I to II essential hypertension [192 men, mean age = 50 ± 8 years, office blood pressure (BP) = 148/95 mmHg] were divided into two groups according to age: Older group (mean age >or = 60 years, n = 43) and younger group (mean age<60 years, n = 252). In all subjects arterial stiffness was evaluated on the basis of carotid to femoral pulse wave velocity (PWV), by means of a computerized method, while ACR values were determined as the mean of two non-consecutive morning spot urine samples. Results: Older compared to younger group had lower office and 24-h diastolic BP (90 ± 8 vs 96 ± 9 mmHg and 74 ± 9 vs 83 ± 9 mmHg, respectively; p < 0.0001 for both), and greater left ventricular mass index (114.3 ± 15 vs 105.2 ± 11 g/m 2, p < 0.05) while did not differ regarding sex, body mass index and metabolic profile (p = NS). Moreover, older compared to younger patients exhibited increased levels of hs-CRP (3.2 ± 0.7 vs 2.1 ± 0.7 mg/l, p < 0.05), ACR (36.5 ± 12 vs 22.8 ± 7 mg/g, p < 0.05) and PWV (8.8 ± 1.5 vs 7.9 ± 1.2 m/sec, p = 0.001). In the entire population, age was associated with hs-CRP (r = 0.120, p < 0.05), ACR (r = 0.221, p < 0.05), and PWV (r = 0.399, p < 0.0001), while it was negatively related to 24-h diastolic BP (r = −0.319, p < 0.0001). Furthermore, hs-CRP was correlated with body mass index (r = 0.281, p < 0.0001) ACR (r = 0.631, p < 0.0001) and PWV (r = 0.233, p < 0.05). In multiple regression analysis, age and hs-CRP were independent predictors of both PWV and ACR (p < 0.05). Analysis of covariance revealed that hs-CRP, ACR and PWV concentrations were significantly different between groups after adjusting for confounders (p < 0.05 for all). Conclusions: Hypertensive patients of more than 60 years of age are characterized by increased levels of hs-CRP, ACR and PWV, whereas the main determinants of early renal dysfunction and arterial stiffness are age and low-grade inflammation. These findings provide an insight into the accelerated atherosclerotic mechanisms of cardiovascular aging.